RECORDS OF PRAYING MANTIDS (INSECTA: MANTODEA) FROM TWO AREAS OF CENTRAL KALIMANTAN, AND NOTES ON BORNEAN ODONTOMANTIS AND HIERODULA - Philip Edward Bragg (BRIN Publishing (Penerbit BRIN), 2021)
Results are presented for a collection of praying mantids from two different habitats in Kalimantan Tengah: an area of peat-swamp forest and an area of hill forest. Forty-one specimens are recorded, representing 20 species; this is the first such collection to be recorded from Kalimantan after more than 70 years. Photographs are included for a number of species, concentrating on species which have not previously been illustrated. Some issues with the Bornean Odontomantis are highlighted and a key to Bornean species is provided. The status of O. micantula Beier, 1937 is clarified, the syntypes are located, and the species is illustrated; the synonymy of O. planiceps and O. javana is questioned. Some historical issues relating to Bornean members of Hierodula are reviewed; the synonymy of H. athene Rehn, 1909 and H. hybrida Burmeister, 1838 and H. venosa (Olivier, 1792) is considered doubtful. Issues with identification of H. venosa and H. vitrea (Stoll, 1813) leave their presence in Borneo questionable.